Pengembangan Media Pembelajaran Interaktif Berbasis APK pada Pembelajaran Olahraga Bolavoli Kelas VII SMP BK ( Bakti Keluarga) Lubuklinggau - Ismail Pulka N; Wawan Syafutra (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga, 2022)
This study aims to develop a learning product in the form of APK-Based Interactive Learning Media Development for Class VII Volleyball Sports Learning at SMP BK (Bakti Keluarga) Lubuklinggau which is valid and practical. This type of research is research and development (R & D) with the development model used is 4D. The research sample or the subject of this study were grade VII students, totaling 9 students. data collection techniques using the percentage value of the score obtained. The results showed that: 1) the quality of interactive learning applications seen from the aspect of validity was included in the valid category with a percentage score of 93,45% and; 2) The quality of interactivelearning applications seen from the practical aspect is categorized as practical, both individual student responses with a percentage score of 90,55%, while the percentage of students' response scores in small groups with a percentage score of 88.33%. So it can be concluded that the apk-based interactive learning application in thematic learning meets the valid and practical criteria so that it can be used in learning Keywords: Apk, Development, Media, SMP, Volleyball